A mitochondria-selective near-infrared-emitting fluorescent dye for cellular imaging studies. Issue 11 (15th June 2018) - Choi, Peter; Noguchi, Katsuya; Ishiyama, Munetaka; Denny, William A.; Jose, Jiney
Graphical abstract: Highlights: A near infrared emitting drug-dye conjugate with selective staining of mitochondria. The synthesis, photo-physical properties, cellular imaging studies reported. Mitochondrial membrane depolarization studies are also reported. Abstract: This communication details the synthesis, evaluation of photophysical properties, and cellular imaging studies of cyanine chromophore based fluorescent dye1 as a selective imaging agent for mitochondria.